CFD Modeling of Structured Packings at Small- and Meso-scale. (July 2017) - Sebastia-Saez, Daniel; Gu, Sai
Abstract: This article presents a CFD model of the multiphase flow inside structured packings for amine-based post-combustion carbon capture. In the literature, simulations are performed at three scales due to computational limitations: small-, meso- and large-scale. This work focuses on small- and meso-scale, introducing interface tracking at both. The interfacial tracking is accomplished by using the Volume of Fluid (VoF) method. Small-scale allows studying the reaction kinetics of the absorption process in 2D geometries. Meso-scale has been used in the literature to describe the dry pressure drop of the packing (single-phase simulations). The interface tracking allows obtaining the relationship between the liquid load and both the liquid hold-up and the interface area. Data from the simulations are compared against experimental results found in the literature. The accurate modeling of the interface area, liquid hold-up and reaction kinetics allows utilizing this CFD model as a design tool for novel packings or to optimizing geometries already in use.